2011
DOI: 10.1186/1475-2859-10-18
|View full text |Cite
|
Sign up to set email alerts
|

Evolution combined with genomic study elucidates genetic bases of isobutanol tolerance in Escherichia coli

Abstract: BackgroundIsobutanol is a promising next-generation biofuel with demonstrated high yield microbial production, but the toxicity of this molecule reduces fermentation volumetric productivity and final titer. Organic solvent tolerance is a complex, multigenic phenotype that has been recalcitrant to rational engineering approaches. We apply experimental evolution followed by genome resequencing and a gene expression study to elucidate genetic bases of adaptation to exogenous isobutanol stress.ResultsThe adaptatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
161
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(169 citation statements)
references
References 93 publications
(205 reference statements)
5
161
3
Order By: Relevance
“…In MexD, a homolog of AcrB in Pseudomonas aeruginosa, SNPs in the large periplasmic loops were detected after selection on carbenicillin in the laboratory and the mutations broadened the resistance spectrum of these bacteria to include β-lactam antibiotics (33). Substitutions within AcrB have been detected following selection with various solvents but, in contrast to this study, the changes tended to be away from the drug-binding pocket and did not alter antimicrobial resistance (34)(35)(36)(37). Mutations at codon 288 of E. coli acrB that were selected in vitro with the efflux pump inhibitor NMP altered susceptibility to efflux pump inhibitors and to some antimicrobial substrates (38).…”
Section: Discussioncontrasting
confidence: 42%
“…In MexD, a homolog of AcrB in Pseudomonas aeruginosa, SNPs in the large periplasmic loops were detected after selection on carbenicillin in the laboratory and the mutations broadened the resistance spectrum of these bacteria to include β-lactam antibiotics (33). Substitutions within AcrB have been detected following selection with various solvents but, in contrast to this study, the changes tended to be away from the drug-binding pocket and did not alter antimicrobial resistance (34)(35)(36)(37). Mutations at codon 288 of E. coli acrB that were selected in vitro with the efflux pump inhibitor NMP altered susceptibility to efflux pump inhibitors and to some antimicrobial substrates (38).…”
Section: Discussioncontrasting
confidence: 42%
“…SetA is an efflux pump capable of transporting different sugars, and the expression of setA was found to be increased under glucose/phosphate stress (5,23), potentially alleviating the accumulation of nonmetabolized sugar phosphates. However, SetA also transports, albeit inefficiently, other substrates, such as the antibiotics kanamycin and neomycin, as well as glucosides and galactosides with alkyl or aryl substituents (6)(7)(8)(9)(10)(11)(12)24). Since there are no sugar analogs in the medium, it is currently unclear whether the overexpression of setA contributes to osmoprotection in MY2 and MY4 mutants.…”
Section: Phenotypic Analyses Of the Isolated Mutants In Multiple Strementioning
confidence: 99%
“…Several nonnative microbial systems have been engineered for its production, including Escherichia coli (1), Lactobacillus brevis (2), Pseudomonas putida (3), Bacillus subtilis (3), and Saccharomyces cerevisiae (4). However, this solvent is highly toxic to microorganisms, imposing a limit on the productivity of bio-based production and leading to the development of simultaneous fermentation and separation techniques to mitigate the toxic effects of the biofuel (5) and efforts to identify the genetic determinants and molecular mechanisms associated with n-butanol tolerance for reverse engineering of more robust strains (6)(7)(8)(9)(10)(11)(12). Prior strain engineering efforts include overexpression of GroESL in Clostridium acetobutylicum (resulting in a 50% improvement in total growth in 0.75% [vol/vol] n-butanol) (12) and recently in E. coli (resulting in a 2.8-fold increase in total growth after 48 h in 0.75% [vol/vol] n-butanol) (11) and overexpression of gene CAC1869 in C. acetobutylicum (resulting in an 81% increase in total growth after 12 h) (13).…”
mentioning
confidence: 99%
“…Thereby, the authors identified a set of mutations (marC, hfq, mdh, acrAB, gatYZABCD, rph) common in several isobutanol tolerant lineages and they speculated that rpoS and post-transcriptional regulators such as hfq are promising targets to improve isobutanol production with E. coli. 14 Since we observed that the best C. glutamicum producer (strain Iso7) showed under aerobic conditions a more than 2-fold lower Y P/S (unpublished results), we tried to transfer the process conditions from the bottle to a bioreactor and thus developed a two phase fermentation. C. glutamicum Iso7 was cultivated in the first phase under aerobic conditions.…”
Section: Discussionmentioning
confidence: 99%